### Need help from an expert?

The world’s top online tutoring provider trusted by students, parents, and schools globally.

The cubic equation with roots 1, -2, and 3 has coefficients -6, 2, -7, and 1.

To find the coefficients of a cubic equation with given roots, we start with the factored form of the equation:

(x - r1)(x - r2)(x - r3) = 0

where r1, r2, and r3 are the roots. Expanding this expression gives:

x^3 - (r1 + r2 + r3)x^2 + (r1r2 + r1r3 + r2r3)x - r1r2r3 = 0

Therefore, the coefficients of the cubic equation are:

a = -1

b = r1 + r2 + r3

c = -(r1r2 + r1r3 + r2r3)

d = r1r2r3

Substituting the given roots, we get:

a = -1

b = 1 + (-2) + 3 = 2

c = -[(1)(-2) + (1)(3) + (-2)(3)] = -(-2 + 3 - 6) = 5

d = (1)(-2)(3) = -6

Therefore, the cubic equation with roots 1, -2, and 3 is:

x^3 + 2x^2 + 5x - 6 = 0

Study and Practice for Free

Trusted by 100,000+ Students Worldwide

Achieve Top Grades in your Exams with our Free Resources.

Practice Questions, Study Notes, and Past Exam Papers for all Subjects!

The world’s top online tutoring provider trusted by students, parents, and schools globally.

Loading...

Loading...